2012
DOI: 10.1126/science.1228606
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking a Myc Enhancer That Includes Human SNP rs6983267 Are Resistant to Intestinal Tumors

Abstract: Multiple cancer-associated single-nucleotide polymorphisms (SNPs) have been mapped to conserved sequences within a 500-kilobase region upstream of the MYC oncogene on human chromosome 8q24. These SNPs may affect cancer development through altered regulation of MYC expression, but this hypothesis has been difficult to confirm. We generated mice deficient in Myc-335, a putative MYC regulatory element that contains rs6983267, a SNP accounting for more human cancer-related morbidity than any other genetic variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(200 citation statements)
references
References 32 publications
6
191
3
Order By: Relevance
“…Additionally, we demonstrate that three of three SNPs previously shown to alter long-range enhancer function [rs12740374/ SORT1 (18) and rs6983267/MYC (19,20)] or to reside in a longrange contact point [rs7578326/IRS1 (21)] overlap a stretch enhancer specifically in the relevant cell type(s) (SI Appendix, Fig. S7 I-K).…”
Section: Significancementioning
confidence: 74%
“…Additionally, we demonstrate that three of three SNPs previously shown to alter long-range enhancer function [rs12740374/ SORT1 (18) and rs6983267/MYC (19,20)] or to reside in a longrange contact point [rs7578326/IRS1 (21)] overlap a stretch enhancer specifically in the relevant cell type(s) (SI Appendix, Fig. S7 I-K).…”
Section: Significancementioning
confidence: 74%
“…On the other hand, a recent mouse model underscores the importance of the rs6983267 enhancer region in colon cancer (Sur et al 2012). Deletion of the enhancer in the mouse germ line had a minor effect on MYC expression but no effect on development, consistent with the lack of eQTL influence in humans.…”
Section: Myc Expression and Cancer Riskmentioning
confidence: 75%
“…Deletion of the enhancer in the mouse germ line had a minor effect on MYC expression but no effect on development, consistent with the lack of eQTL influence in humans. In contrast, crossing the rs6983267 enhancer-deficient line to the "APCmin" mouse, which harbors a germ line mutation in the APC tumor suppressor, leads to a dramatic reduction in intestinal tumor development (Sur et al 2012). These observations provide a graphic demonstration of the essential role of the rs6983267 enhancer as a "target" of the excessive Wnt signaling found in colon cancers.…”
Section: Myc Expression and Cancer Riskmentioning
confidence: 99%
“…28,29 Indeed, this connection intensified following reports that the 8q24 locus revealed by GWAS of a number of cancers, including colorectal carcinomas, was due to an extreme upstream TCF7L2-binding element driving the transcription of MYC. [30][31][32] In addition, it has been shown that when TCF7L2 recurrently fuses with its neighboring gene, VTI1A, colorectal adenocarcinomas result. Curiously, many of the other GWASimplicated loci associated with T2D are also associated with the risk for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%